1988
DOI: 10.1051/jphys:01988004902030700
|View full text |Cite
|
Sign up to set email alerts
|

A synchrotron X-ray study of competing undulation and electrostatic interlayer interactions in fluid multimembrane lyotropic phases

Abstract: 2014I1 a récemment été mis en évidence, en utilisant une méthode de diffraction des rayons X, le rôle prédominant des interactions d'ondulation lors de la dilution par du dodécane d'une phase lamellaire d'un mélange quaternaire lyotrope [1]. Afin d'étudier la compétition entre les interactions d'ondulation et les forces électrostatiques, nous avons étudié l'effet de la dilution avec, soit de l'eau, soit de la saumure (~ 0,5 mole. 1-1 NaCl), sur les interactions d'une phase lamellaire L03B1. Dans ces deux cas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
224
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(244 citation statements)
references
References 20 publications
16
224
0
3
Order By: Relevance
“…This complicated behavior seems to indicate that in terms of η , a most hydrophilic l-menthol has the highest efficiency for liquefying the cationic bilayer membranes among the investigated fragrance components. If the membranes are stabilized almost exclusively by electrostatic interactions, small values of η ≈ 0.1 are expected 15,16,25,26 . For the present industrially relevant cationic systems, we obtain η 1, which, strictly speaking, seems to be already beyond the application limit of the modified Caillé model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This complicated behavior seems to indicate that in terms of η , a most hydrophilic l-menthol has the highest efficiency for liquefying the cationic bilayer membranes among the investigated fragrance components. If the membranes are stabilized almost exclusively by electrostatic interactions, small values of η ≈ 0.1 are expected 15,16,25,26 . For the present industrially relevant cationic systems, we obtain η 1, which, strictly speaking, seems to be already beyond the application limit of the modified Caillé model.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many of these products are thermodynamically unstable though they are to be equipped with sufficiently long temporal stability. Here, we have investigated structural details of cationic vesicles prepared from TEQ surfactant comprising mono-, di-, and tri-ester components, in which we use cryogenic transmission electron microscopy cryo-TEM 28 30 , small angle X-ray scattering SAXS 15,16,20,25,26,27 , and electron spin resonance ESR spectroscopy 31 39 . The major component of the TEQ surfactant is di alkyl fatty ester quaternary ammonium methosulfate.…”
Section: Introductionmentioning
confidence: 99%
“…That the swelling is limited may be due to local Van der Waals attractions where two fluctuating interfaces come close together and the relatively weak attractions are reinforced by small separations and a large area. However, both theoretical [32] and experimental [33] work indicate that due to undulations of the surfactant layers, the net interactions are in general repulsive rather than attractive. A rather successful phenomenological theory [34] considers middle phase microemulsions as ensembles of non-interacting monolayers.…”
Section: Mvp Hi:11j141j11mentioning
confidence: 99%
“…This phase corresponds to layers of water surounded with surfactant separated with dodecane. It is stabilized by undulation interactions [7]. Using Couette cells and different techniques, we have shown that a shear diagram can be described corresponding to different orientations of the smectic layers respecting the flow field [5] (see Fig.…”
Section: Reofêsicas De Fases Laminaresmentioning
confidence: 99%